An Endohyphal Bacterium (Chitinophaga, Bacteroidetes) Alters Carbon Source Use by Fusarium keratoplasticum (F. solani Species Complex, Nectriaceae) - Shaffer, Justin P.; U'Ren, Jana M.; Gallery, Rachel E.; Baltrus, David A.; Arnold, A. Elizabeth (Frontiers in Microbiology, 2017)
Bacterial endosymbionts occur in diverse fungi, including members of many lineages of Ascomycota that inhabit living plants. These endosymbiotic bacteria (endohyphal bacteria, EHB) often can be removed from living fungi by antibiotic treatment, providing an opportunity to assess their effects on functional traits of their fungal hosts. We examined the effects of an endohyphal bacterium (Chitinophaga sp., Bacteroidetes) on substrate use by its host, a seed-associated strain of the fungus Fusarium keratoplasticum, by comparing growth between naturally infected and cured fungal strains across 95 carbon sources with a Biolog® phenotypic microarray. Across the majority of substrates (62%), the strain harboring the bacterium significantly outperformed the cured strain as measured by respiration and hyphal density. These substrates included many that are important for plant- and seed-fungus interactions, such as D-trehalose, myo-inositol, and sucrose, highlighting the potential influence of EHB on the breadth and efficiency of substrate use by an important Fusarium species. Cases in which the cured strain outperformed the strain harboring the bacterium were observed in only 5% of substrates. We propose that additive or synergistic substrate use by the fungus-bacterium pair enhances fungal growth in this association. More generally, alteration of the breadth or efficiency of substrate use by dispensable EHB may change fungal niches in short timeframes, potentially shaping fungal ecology and the outcomes of fungal-host interactions.